Kulturowy i teologiczny wymiar feminizmu - Obirek, Stanisław (Przegla̜d religioznawczy, 2021)
The main purpose of this article is to present feminist theology as an integral part of contemporary feminism. In the author's opinion, the omission of this diverse and revolutionary in its consequences theological field is the cause of an apparent conflict between mainstream feminism and theology. Hence the review nature of the article presenting significant achievements of feminist theology. One of them is a positive approach to human corporeality, especially sexuality, which happens in response to traditional approaches, often hostile to these dimensions of human existence. However, the most important achievement of theological feminism is a paradigm shift in the approach to the place of women in three monotheistic religions: Judaism, Christianity and Islam. Therefore, these three religious traditions are presented in detail.